Significados espaciales en contexto de transformación urbana y revitalización patrimonial de habitantes adultos y locatarios del barrio La Ronda, del Centro Histórico del Distrito Metropolitano de Quito. - Vacacela Zerga, José Luis (2012)
This research is in the field of environmental psychology community, which seeks to understand the relationship between people and environment and the dynamics of social relations linked to land-transformation approach. This field is explored within the context of Ecuador, since there are no research background in neighborhood and community contexts within the country. Thus, this study set evolution analysis and categories of Place Attachment, Place Identity, Sense of Community and Community Participation.